SÜRDÜRÜLEBİLİRLİK RAPORLAMASINDA ÖLÇÜM_x000D_ PARAMETRELERİ KPI’LAR (TEMEL PERFORMANS_x000D_ GÖSTERGELERI): BANKACILIK SEKTÖRÜNDE ANALİZ - ÖKTEM, BEGÜM (My University, 2019)
Bu çalışmada öncelikle sürdürülebilirlik raporunun kapsamına yer verilerek, işletmelerin sürdürülebilirlikraporu hazırlama ve hazırlamama nedenleri ile sürdürülebilirlik raporlama süreci belirtilmiştir. Ardındansürdürülebilirlik ölçümünde önem arz eden Temel Performans Göstergeleri (KPI)’nin belirlenmesi sırasındadikkate alınması gereken kriterler belirlenerek, sürdürülebilirlik boyutları açısından sınıflandırılması ile eldeedilen ekonomik, sosyal ve çevresel KPI parametrelerine yer verilmiştir. Açıklanan parametreleri somut halegetirebilmek için bankacılık sektöründe belirlenen üç kurumsal bankada sürdürülebilirlik raporu ve TemelPerformans Göstergelerinin durumu analiz edilerek, çalışma sonlandırılmıştır.

In this study, first of all, the sustainability report has been covered and the sustainability reporting_x000D_ process and the reasons for not preparing and preparing the sustainability report are stated. Then,_x000D_ the criteria that must be taken into consideration during the determination of the Key Performance_x000D_ Indicators (KPI) which are important in the measurement of sustainability are determined and the_x000D_ economic, social and environmental Key Performance Indicators (KPI) parameters obtained by the_x000D_ classification in terms of sustainability dimensions are included. In order to concrete the explained_x000D_ parameters, the results of the sustainability report and the Basic Performance Indicators were analyzed in the three corporate banks determined in the banking sector and the study was terminated.
MEASUREMENT PARAMETERS IN SUSTAINABILITY REPORTING KPI’S (KEY PERFORMANCE INDICATORS): ANALYSIS IN BANKING SECTOR